Peace, justice and disabled women’s advocacy: Tamil women with disabilities in rural post-conflict Sri Lanka - Kandasamy, N.; Soldatic, Karen; Samararatne, D. (2017)
© 2016 Informa UK Limited, trading as Taylor & Francis GroupThis article draws on grounded qualitative research with rural Tamil women who acquired a disability during the civil war in Sri Lanka and conceptualizes an intersectionality-peace framework. Three main themes were developed from the interviews: narratives of conflict, survival outcomes of social assistance and mobilization of cross-ethnic relationships. With the support of a local women’s disability advocacy organization, Tamil women with disabilities were enabled to overcome social stigma and claim a positive identity as women with disabilities. The organization’s focus on realizing disability rights created new opportunities for these highly marginalized rural women. The women were also supported to form cross-ethnic relationships with women who similarly faced multiple oppressions. These relationships transformed the women into ‘agents of peace’, using their newfound disability identity to foster cross-ethnic dialogue and create safe spaces in the post-conflict context.